Impact of geographic location and place of surgery on treatment outcomes of total hip replacement - Slavko Manojlovic; Dragana Dragicevic-Cvjetkovic; Nemanja Manojlović; Zeljko Jovičić; Mirko Manojlović; Ferid Krupić (Medicinski glasnik, 2026)
Introduction: Environmental factors may influence postoperative outcomes and quality of life following total hip replacement (THR). This study investigated the impact of the geographical location of the surgical site, as well as the patient’s place of birth and residence, on treatment outcomes in individuals with artificial hips. Methods: A prospective study was conducted involving 280 patients (both genderes; mean age 62 ± 8.8 years) who underwent THR due to primary or secondary hip osteoarthritis. Patients were divided into two groups: Group A (n = 64) included individuals who were not operated on in their place of birth and residence, while Group B (n = 216) consisted of those who were born, resided, and underwent surgery in the same geographical location. Outcomes were assessed using the EQ-5D questionnaire (covering mobility, self-care, usual activities, pain/discomfort, and anxiety/depression), the Visual Analogue Scale (VAS) for pain, and a VAS-based treatment satisfaction scale, administered preoperatively and one year postoperatively. Statistical analysis was performed using Fisher’s exact test (p < 0.05). Results: Only 22.9% of all patients underwent surgery in their place of birth and residence, mostly for primary hip osteoarthritis. Preoperatively, Group A reported significantly greater limitations in self-care (p < 0.05). One year postoperatively, Group B showed significantly higher VAS scores for treatment satisfaction (p < 0.05). Conclusion: Patients who underwent total hip replacement in their place of birth and residence demonstrated better postoperative outcomes compared to those who had relocated. Keywords: : arthroplasty; immigrants; quality of life
Keywords: arthroplasty; immigrants; quality of life